2022
DOI: 10.1109/tgrs.2022.3226631
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Water Vapor Content at High Spatio-Temporal Resolution Using a Network of Low-Cost Multi-GNSS Receivers

Abstract: The Global Navigation Satellite System (GNSS) has the capacity for remote sensing of water vapor content in the atmosphere. Post-processing of GNSS data can provide Integrated Water Vapor (IWV) with accuracies comparable to measurements of traditional sensors, i.e. water vapor radiometers. While GNSS meteorology benefits from thousands of permanent GNSS stations operating worldwide the spatial resolution of GNSS-derived IWV is limited to tens of kilometers. Further densification of GNSS networks is achievable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Also, the topography of Wrocław city is rather flat which results in similar altitudes of all GNSS receivers within the network (maximum height difference between the stations equal to 25 m); it is a limiting factor in the tomographic reconstruction of the wet refractivity fields (Rohm andBosy 2009, 2011). In the paper by Marut et al (2022) it was proven that the low-cost GNSS receivers are able to provide 2-D information about water vapour distribution in the troposphere on the level of 1.0-1.5 kg m −2 IWV. It shows the ability of the low-cost receivers to provide water vapour distribution on the city scale, which was also shown in our research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the topography of Wrocław city is rather flat which results in similar altitudes of all GNSS receivers within the network (maximum height difference between the stations equal to 25 m); it is a limiting factor in the tomographic reconstruction of the wet refractivity fields (Rohm andBosy 2009, 2011). In the paper by Marut et al (2022) it was proven that the low-cost GNSS receivers are able to provide 2-D information about water vapour distribution in the troposphere on the level of 1.0-1.5 kg m −2 IWV. It shows the ability of the low-cost receivers to provide water vapour distribution on the city scale, which was also shown in our research.…”
Section: Discussionmentioning
confidence: 99%
“…3). A detailed description of the receivers and the GNSS data processing strategy can be found in Marut et al (2022). The receivers are based on the u-blox high-precision GNSS module (ZED-F9P), microcomputer Raspberry Pi 3B+, and the GSM modem.…”
Section: Gnss Tropospheric Delaysmentioning
confidence: 99%
See 1 more Smart Citation
“…A S AN emerging and novel method for the sensing of atmospheric parameters, the ground-based global navigation satellite systems (GNSSs) tropospheric sounding technique has undergone unprecedented development in recent decades [1], [2], [3], [4]. Multiple products obtained from this technique, e.g., zenith total delay (ZTD) and precipitable water vapor (PWV), are known to have the advantageous features of high accuracy, high spatiotemporal resolution, all-weather, low cost, and free of instrumental bias [5], [6], [7], [8], [9]. Therefore, this advanced technique has offered strong data support and opened new opportunities to enhance our understanding of atmospheric conditions, climate phenomena, and weather extremes [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Ste ¸pniak and Paziewski [37] confirmed these findings by comparing solutions from the ZED-F9P using different antenna types to tropospheric delays from ray-tracing. In a recent study, Marut et al [38] showed the usability of the ZED-F9P for retrieval of ZTD and integrated water vapor (IWV) in a very dense network, covering the city of Wroclaw, Poland. Validation of their results using estimates from geodetic-grade GNSS receivers and a co-located water vapor radiometer showed satisfactory performance of the proposed station setup.…”
Section: Introductionmentioning
confidence: 99%